Historical human exposure to perfluoroalkyl acids in the United States and Australia reconstructed from biomonitoring data using population-based pharmacokinetic modelling. (November 2017) - Gomis, Melissa I.; Vestergren, Robin; MacLeod, Matthew; Mueller, Jochen F.; Cousins, Ian T.
Abstract: Perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS) and perfluorohexanesulfonic acid (PFHxS) are found in the blood of humans and wildlife worldwide. Since the beginning of the 21st century, a downward trend in the human body burden, especially for PFOS and PFOA, has been observed while there is no clear temporal trend in wildlife. The inconsistency between the concentration decline in human serum and in wildlife could be indicative of a historical exposure pathway for humans linked to consumer products that has been reduced or eliminated. In this study, we reconstruct the past human exposure trends in two different regions, USA and Australia, by inferring the historical intake from cross-sectional biomonitoring data of PFOS, PFOA and PFHxS using a population-based pharmacokinetic model. For PFOS in the USA, the reconstructed daily intake peaked at 4.5 ng/kg-bw/day between 1988 and 1999 while in Australia it peaked at 4.0 ng/kg-bw/day between 1984 and 1996. For PFOA in the USA and Australia, the peak reconstructed daily intake was 1.1 ng/kg-bw/day in 1995 and 3.6 ng/kg-bw/day in 1992, respectively, and started to decline in 2000 and 1995, respectively. The model could not be satisfactorily fitted to the biomonitoring data for PFHxS within reasonable boundaries for its intrinsic elimination half-life, and thus reconstructing intakes of PFHxS was not possible. Our results indicate that humans experienced similar exposure levels and trends to PFOS and PFOA in the USA and Australia. Our findings support the hypothesis that near-field consumer product exposure pathways were likely dominant prior to the phase-out in industrialized countries. The intrinsic elimination half-life, which represents elimination processes that are common for all humans, and elimination processes unique to women (i.e., menstruation, cord-blood transfer and breastfeeding) were also investigated. The intrinsic elimination half-lives for PFOS and PFOA derived from model fitting for men were 3.8 and 2.4 years, respectively, for the USA, and 4.9 and 2 years respectively for Australia. Our results show that menstruation is a depuration pathway for PFOA for women, similarly but to a lesser extent compared to previous reports for PFOS. However menstruation, cord-blood transfer and breastfeeding together do not fully explain the apparently more rapid elimination of PFOA and PFOS by women compared to men; the intrinsic elimination half-lives in women were up to 13% lower for PFOS and up to 12% lower for PFOA compared to the corresponding half-lives in men. Highlights: The historical intake of PFOS, PFOA and PFHxS were recreated for the American and Australian population and compared. The fitted elimination half-life for PFOS and PFOA were within the range of values reported in other studies. Similar historical intake were found for PFOS and PFOA in both countries suggesting an exposure via consumer products. The model was unable to describe the concentration-time trend of PFHxS in neither the American nor the Australian population.